Enzymatic degradation of Polysaccharide-based layer-by-layer structures - Cardoso, M. J. (2016)
The lack of knowledge on the degradation of layer-by-layer structures is one of the causes hindering its translation to preclinical assays. The enzymatic degradation of chitosan/hyaluronic acid films in the form of ultrathin films, freestanding membranes, and microcapsules was studied resorting to hyaluronidase. The reduction of the thickness of ultrathin films was dependent on the hyaluronidase concentration, leading to thickness and topography variations. Freestanding membranes exhibited accelerated weight loss up to 120 h in the presence of the enzyme, achieving complete degradation. Microcapsules with around 5 Î¼m loaded simultaneously with FITC-BSA and hyaluronidase showed that the coencapsulation of such enzyme and protein mixture led to a FITC-BSA release four times higher than in the absence of hyaluronidase. The results suggest that the degradation of LbL devices may be tuned via embedded enzymes, namely, in the controlled release of active agents in biomedical applications.